2006
DOI: 10.4049/jimmunol.177.6.3669
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Expression on Activated NK Cells: Ligation of CD4 Induces Cytokine Expression and Cell Migration

Abstract: NK cells play an important role in the innate immune response. We have isolated NK cells from human lymphoid tissues and found that these cells express the CD4 molecule on their surface at levels higher than those found on peripheral blood NK cells. To study the functional role of the CD4 molecule on NK cells, we developed an in vitro system by which we are able to obtain robust CD4 expression on NK cells derived from blood. CD4+ NK cells efficiently mediate NK cell cytotoxicity, and CD4 expression does not ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 34 publications
4
57
0
4
Order By: Relevance
“…17 In agreement with a previously published report, 25 we observed a distinct population of peripheral blood CD56 ϩ CD3/14/ 19 neg cells expressing CD4 ( Figure 1A) that comprised 0.2% to 7.5% of the peripheral blood CD56 ϩ cell population ( Figure 1B) within the lymphocyte gate. To distinguish between CD4 ϩ CD56 ϩ NK cells and other potentially contaminating cell types, such as monocytic or dendritic cells, we used CD7 as an additional NK cell-specific marker.…”
Section: Cd7 Identifies 2 Subsets Of Cd4 ؉ Cd56 ؉ Cellssupporting
confidence: 81%
See 3 more Smart Citations
“…17 In agreement with a previously published report, 25 we observed a distinct population of peripheral blood CD56 ϩ CD3/14/ 19 neg cells expressing CD4 ( Figure 1A) that comprised 0.2% to 7.5% of the peripheral blood CD56 ϩ cell population ( Figure 1B) within the lymphocyte gate. To distinguish between CD4 ϩ CD56 ϩ NK cells and other potentially contaminating cell types, such as monocytic or dendritic cells, we used CD7 as an additional NK cell-specific marker.…”
Section: Cd7 Identifies 2 Subsets Of Cd4 ؉ Cd56 ؉ Cellssupporting
confidence: 81%
“…The only significant difference observed in this study pertained to the activation status of the CD7 ϩ CD4 ϩ NK cells. In agreement with a previous report proposing that CD4 ϩ NK cells are activated and capable of producing cytokines, 25 we observed that a significantly greater percentage of CD7 ϩ CD4 ϩ NK cells express the T helper 1 chemokine receptor CXC chemokine receptor 3 (CXCR3) and possess significantly higher levels of glucocorticoid-induced tumor necrosis factor (TNF) receptor (GITR; Figure 3L-M). We also observed that approximately 30% and 18% of the IFN␥ ϩ NK cells express CD4 after IL-12 plus IL-18 and K562 stimulation, respectively (data not shown).…”
Section: Only Cd7 ؉ Cd56 ؉ Cells Express Nk Cell-associated Receptorssupporting
confidence: 81%
See 2 more Smart Citations
“…Coexpression of CD244 and CD3 was used to identify CD28 null T cells. To exclude CD4 dim macrophages/monocytes and NK cells which also might express CD244 (25), the combination of CD3 and CD4 in the three-color stainings was used to identify CD4 ϩ T cells. To identify CD8 ϩ T cells in the very same section, a lack of CD4 in presence of CD3 was used.…”
Section: Muscle Biopsy Tissue and Immunostainingsmentioning
confidence: 99%